Marketing caused in times of coronavirus (Revista de Investigaciones Universidad del Quindío, 2021)
This document is the result of the analysis of a documentary and cybergraphic review divided into two parts, the first to review the concepts of marketing, social marketing and marketing with a cause, the second consisted of reviewing the companies that applied Marketing strategies with a cause in the COVID-19 pandemic during the period from April 2020 to March 2021 to understand how these, through their activities, helped society and the government sector to face this situation, but especially in the health sector. These companies managed to create alliances with non-profit organizations to improve their image and loyalty as well as that of their products or services, hoping to be seen as socially responsible companies that helped the community while benefiting from increasing their sales.
Keywords: Marketing; marketing with a cause; COVID-19